Creating a lean and green business system techniques for improving profits and sustainability - Zokaei, A. Keivan (Boca Raton Taylor & Francis Group, 2013)
Things that are good for the planet are also good for business. Numerous studies from the likes of the Economist Intelligence Unit, Harvard, MIT Sloan, and others indicate that organizations that commit to goals of zero waste, zero harmful emissions, and zero use of nonrenewable resources clearly outperform their competition.
Includes bibliographical references and index.
Keywords: Industrial management--Environmental aspects